Characterization of coal fly ash and use of plants growing in ash pond for phytoremediation of metals from contaminated agricultural land. Issue 4 (21st March 2018) - Kisku, Ganesh Chandra; Kumar, Vinay; Sahu, Pokhraj; Kumar, Pramod; Kumar, Narendra
ABSTRACT: Mobilization of heavy metals around coal power plants due to improper disposal of fly ash (FA) and wastewater have led to release of pollutants into the environment. For protection of inimitable natural resources, application of economical and effective technologies is needed such as phytoremediation is cost-effective, ecofriendly and a better option for elimination of metal from contaminated sites. Twelve plant species were sampled from ash dyke of Singrauli and screened for accumulation of metals for this study. Mobilization ratio of metals from soil to plant was evaluated to determine translocation factor. CILLAS analyzer, Raman spectroscopy and SEM-EDX were used for characterization of particle size, functional groups and morphology of fly ash. Results showed mean metal concentrations in contaminated soil for Fe, Mn, Cr, Zn, Ni, Cu, Cd and Pb were 909.4, 60.6, 9.5, 134.8, 13.6, 26.7, 2.9 and 25.4 µg g −1 respectively. Enrichment factors for soil, root and shoot for a contaminated site were 1.9, 3.8 & 4.3 for Zn and 2.7, 3.5 & 3.8 for Cd. Six hyper-accumulators with absorption efficiency >1 viz. I. carnea, S. nigrum, S. munja, T. angustifolia, C. dactylon and P. hysterophorus were identified which may be cultivated successively to reclaim and restore damaged agricultural land.